2006
DOI: 10.3137/ao.440405
|View full text |Cite
|
Sign up to set email alerts
|

Climatological features of orographic low‐level jets over frobisher bay

Abstract: In this study, based on an analysis of operational hourly surface and 12-hourly upper air data, the seasonal and diurnal climatological features of orographic low-level jets and associated vertical wind shear over Frobisher Bay, southern Baffin Island are discussed. These strong winds are a common phenomenon and frequently lead to hazardous flying conditions and hardship on the ground. The influence of the surrounding topography causes significant channelling of the surface wind at Iqaluit, with prevailing win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…1), and they attributed the dominance of the strong northwesterly and north-northwesterly surface winds in winter to topographically induced wind channelling. In agreement with Hudson et al (2001), the analysis of surface winds recorded at Iqaluit over a 21-year period performed by Nawri and stewart (2006) revealed that the northwesterly and southeasterly surface winds together accounted for more than 80% of all hourly observations of strong surface winds (>10 m s -1 ). The highest occurrence of strong winds was in October-March.…”
Section: B Previous Worksupporting
confidence: 65%
See 2 more Smart Citations
“…1), and they attributed the dominance of the strong northwesterly and north-northwesterly surface winds in winter to topographically induced wind channelling. In agreement with Hudson et al (2001), the analysis of surface winds recorded at Iqaluit over a 21-year period performed by Nawri and stewart (2006) revealed that the northwesterly and southeasterly surface winds together accounted for more than 80% of all hourly observations of strong surface winds (>10 m s -1 ). The highest occurrence of strong winds was in October-March.…”
Section: B Previous Worksupporting
confidence: 65%
“…Moreover, Nawri and stewart (2008) found that cyclones provided conditions, through the associated large-scale pressure field, for both sustained and strong surface winds at Iqaluit along either the northwest or southeast direction and sudden shifts between these prevailing directions. Nawri and stewart (2006) also investigated the vertical structure of winds with surface speeds greater than 10 m s -1 using operational 12 h soundings at Iqaluit. The mean vertical profiles corresponding to northwesterly surface winds during the winter (January-March) showed an orographic low-level jet reaching its maximum speed at the surface.…”
Section: B Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Topographic effects can also result in high wind speed (gap and barrier flows) and significant precipitation events (e.g., Martin and Moore 2005; Nawri and Stewart 2006. Occasionally, strong northeasterlies may reach the surface in Iqaluit, or they may generate intense horizontal vortices (rotors) at the sharp rise of the terrain (e.g., Ozawa et al 1998;Hudson et al 2001).…”
mentioning
confidence: 99%
“…Climatologically, wind speeds above 90 km h −1 occur fewer than once a year, in either autumn or winter. However, strong low-level jets with hourly wind speeds greater than 60 km h −1 are reported about 25 times a year on average, mainly from autumn to spring and primarily from the northwest Stewart 2006, 2008).…”
mentioning
confidence: 99%